HUBUNGAN ANTARA TINGKAT PENGETAHUAN TENTANG KANKER SERVIKS DENGAN MOTIVASI MELAKUKAN PEMERIKSAAN PAP SMEAR PADA IBU RUMAH TANGGA DI DESA GULUNAN SIDOKERTO KECAMATAN PLUPUH KABUPATEN SRAGEN - Rahayu Setyaningsih; Endang Dwi Ningsih; Bagus Permadi (KOSALA : Jurnal Ilmu Kesehatan, 2014)
Abstract Background The interviews with housewives in the village Gulunan Sidokerto, most say not to know about cervical cancer and the dangers, so that people's motivation for the early detection of cervical cancer is also lower than all the proven mother in the village has never been anyone doing a Pap test. The purpose of this study was to determine the relationship between the level of knowledge about cervical cancer with a Pap smear examination motivation housewives in the village of Subdistrict Plupuh Gulunan Sidokerto Sragen. Subjects were mothers of the population in the village of 45 people Gulunan Sidokerto number by looking at the table Krecji, samples found as many as 40 people. This research is analytic, the research design and approach of cross -sectional correlation. The sampling technique used is nonpropability sampling is purposive sampling . Data analyzed by chi-square test with p = 0.05 , obtained p value of 0.004 to p < 0.05 , which means that Ho is rejected and Ha accepted . The conclusion of the study. There is a relationship between the level of knowledge of cervical cancer with the Pap smear examination motivation housewives in the village of Subdistrict Plupuh Gulunan Sidokerto Sragen with p= 0.004 . Keywords : Knowledge Level, Cervical Cancer, Motivation, Pap Smear .